Deep End-to-end Causal Inference - Geffner, Tomas; Antoran, Javier; Foster, Adam; Gong, Wenbo; Ma, Chao; Kiciman, Emre; Sharma, Amit; Lamb, Angus; Kukla, Martin; Hilmkil, Agrin; Jennings, Joel; Pawlowski, Nick; et al. (NeurIPS 2022 Workshop on Causal Machine Learning for Real-World Impact (CML4Impact 2022), 2022)
Causal inference is essential for data-driven decision making across domains such as business engagement, medical treatment and policy making. However, research on causal discovery has evolved separately from causal inference, preventing straightforward combination of methods from both fields. In this work, we develop Deep End-to-end Causal Inference (DECI), a non-linear additive noise model with neural network functional relationships that takes in observational data and can perform both causal discovery and inference, including conditional average treatment effect (CATE) estimation. We provide a theoretical guarantee that DECI can asymptotically recover the ground truth causal graph and treatment effects when correctly specified. Our results show the competitive performance of DECI when compared to relevant baselines for both causal discovery and (C)ATE estimation in over a thousand experiments on both synthetic datasets and causal machine learning benchmarks.